Health promotion of families and “PAUD” teachers in improving cognition, commitment and behavior to prevent covid-19 transmission in children - Ulva Noviana; heni ekawati (Jurnal Keperawatan, 2022)
Introduction:  Indonesia was entering the Covid-19 emergency response period, as indicated by the increase in Covid-19 cases and the risk of transmission in high-risk groups, one of which is children. The increase in Covid-19 cases has not been followed by compliance with Covid transmission prevention behavior in the community, especially among children. Objectives: This research aims to improve the cognition, commitment, and behavior of Covid 19 prevention during the Covid emergency through the Health Promotion of families and kindergarten teachers. Methods: The research design used is the Quasy Experiment, with a large sample of 100 pre-school age children divided into two groups, simple sampling techniques random sampling, Independent variables: Health promotion of families and teachers using pocketbook media, children's AKB Logbook, Educational Videos, and Variable dependents: cognition, commitment and preventive behavior of Covid 19 in pre-school children. The instrument used is a questionnaire, a Statistical test using Wilcoxon Rank Test, Pair T-Test, and Mann Whitney. Results:  The results of the study found that health promotion using pocketbooks, AKB logbooks, Whatsapp Groups media, and Educational videos were able to improve cognition, commitment, and behavior of Covid 19 prevention because it provides information directly to families and teachers. For seven days, the child, under the supervision, assistance, and facilitation of teachers, performs Prokes in school and, through the help of parents, carries out the process at home. This helps children get used to adapting to new life in a Covid emergency. Conclusions: there is an improvement in cognition, commitment, and preventive behavior of Covdi 19 in children after being given Health Promotion.